Crucial problems in arranged the lesson plan of vocational teacher - Muhammad Nurtanto; Nur Kholifah; Alias Masek; Putu Sudira; Achmad Samsudin (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study aimed to explore the implementation of the 2013 curriculum in vocational schools, Banten in terms of the readiness and quality of the learning tools that have been prepared. A total of 957 respondents from 2017 to 2018, consisting of four cities and three districts in Banten Province were involved in the training and mentoring program, namely vocational teachers and vice-principals in the curriculum field. Data were collected using questionnaire sheets, FGD notes, and observation check dates. The data obtained are analyzed and interpreted based on the specified categories. The results showed that: 1) Teacher readiness for learning tools in the components a) Core Competencies (CC) and Basic Competencies (BC) analysis of 45.31%, b) Program mapping of 38.37%, learning plan preparation of 39.45% and c) Learning evaluation of 36.78%; 2) The quality of lesson plan (LP) the science lesson plan analysis instrument (SLPAI) based is divided into two groups. The category "Quality" in the instructional program and instructional plan aspects, and the category "Moderate" in the instructional media and assessment and others aspects; and 3) The difficulty of learning device components, including authentic assessment, use of methods, literacy approaches, and lesson planning. The implementation of training, mentoring, and supervision programs are adjusted to the experience of vocational teachers taking into account the teacher's involvement in the implementation of the curriculum, age, and school readiness.